2 in 1 plate / Mohd Fitri Azha … [et al.] - Azha, Mohd Fitri; Abdul Latif, Norfazliawati; Abdul Halim, Noor Hamira; Salim, Siti Noraini; Rahim, Nurul Afiqah; Harun, Norazman; Omar, Roaimah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Courseware has been used people nowadays. It not only helps us to understand something better, but it also can help us to practice it manually. Like what will we make is courseware on how to learning drive. As we all know, driving license not only taken by young people but also those who are older. With this courseware, it can help them to understand more because the information also has in pictures. They also can learn it as long as they want and can be repeated again and this will help them to remember with easily. Indirectly, they can make preparation before to the actual driving test. This courseware contains complete of a driving test as the test parking, up the hill and so on. So, with this courseware, it will help those who will stand the test drive JPJ to know a bit about the learning system and how their scoring system.